Research in Attacks, Intrusions, and Defenses 16th International Symposium, RAID 2013, Rodney Bay, St. Lucia, October 23-25, 2013, Proceedings - Stolfo, Salvatore J.; Stavrou, Angelos; Wright, Charles V. (Security and Cryptology, 2013)
This book constitutes the proceedings of the 16th International Symposium on Research in Attacks, Intrusions and Defenses, former Recent Advances in Intrusion Detection, RAID 2013, held in Rodney Bay, St. Lucia in October 2013. The volume contains 22 full papers that were carefully reviewed and selected from 95 submissions, as well as 10 poster papers selected from the 23 submissions. The papers address all current topics in computer security ranged from hardware-level security, server, web, mobile, and cloud-based security, malware analysis, and web and network privacy.